Freelancer Management Information System Integrating PSAK 72 and PPh 21 - Rima Dewanti Suwardani; Edy Anan; Muhammad Agung Reza Yudha (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to design and implement a web-based freelancer management information system that integrates operational management, financial recording based on PSAK 72, and tax calculation for non-employee income (PPh 21). The rapid growth of freelancers in the gig economy has not been accompanied by integrated systems that support booking management, structured financial recording, and accurate tax calculation, resulting in inefficiencies and potential reporting errors. This study employs the Design Science Research (DSR) approach, ith system requirements analyzed using the PIECES framework and system development conducted through the Waterfall model. Data were collected through observation and interviews with six freelancers in the creative service sector. The developed system includes features such as booking management, recording of down payments (DP) and settlements, revenue recognition based on PSAK 72, and automatic PPh 21 calculation using the non-employee tax scheme. The evaluation results indicate improvements across all PIECES aspects, particularly in performance (4.50) and efficiency (4.28). The implementation of PSAK 72 ensures that down payments are recorded as liabilities and recognized as revenue only after performance obligations have been fulfilled. Additionally, the integrated tax calculation feature improves users’ understanding of tax obligations and reduces calculation errors. This study contributes by providing an integrated system that combines operational, accounting, and taxation aspects within a single platform.